Measures of strategic alliance performance: an analysis of construct validity - Ariño, Africa (Journal of International Business Studies, 2003)
This study evaluates the construct validity of measures of the performance of strategic alliances in 34 equity strategic alliances (SAs) and 45 contractual SAs. We discuss the content validity of existing measures in the light of current concepts of SA performance. Empirical results show that the fulfilment of strategic goals, and other organizational effectiveness measures of SA performance – such as overall performance satisfaction and net spillover effects – capture different underlying factors. The latter two measures display convergent validity. The results also support the discriminant validity of these two measures with respect to contractual changes and survival, but not with respect to longevity. Building on our findings, we propose an expanded definition of SA performance that considers both outcome and process performance.